2016
DOI: 10.1002/pip.2818
|View full text |Cite
|
Sign up to set email alerts
|

Failure analysis on lattice matched GaInP/Ga(In)As/Ge commercial concentrator solar cells after temperature accelerated life tests

Abstract: Accelerated life tests are frequently used to provide reliability information in a moderate period of time (weeks or months), and after that, a failure analysis is compulsory to detect the failure origins. In this paper, a failure analysis has been carried out after a temperature accelerated life test on lattice matched GaInP/Ga(In)As/Ge triple junction commercial solar cells. Solar cells were forward biased in darkness inside three climatic chambers in order to emulate the photo-generated current under nomina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…This result suggests the need of some improvement in the CPV cell or in the module heat extraction for proper operation in Tucson. Fortunately, this does not seem a hard task because we have recently shown that the failure origin of these cells is related with the front metal grid and its external connection and not the semiconductor structure .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This result suggests the need of some improvement in the CPV cell or in the module heat extraction for proper operation in Tucson. Fortunately, this does not seem a hard task because we have recently shown that the failure origin of these cells is related with the front metal grid and its external connection and not the semiconductor structure .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, if the failure associated with the front metal grid connection detected in the analysed solar cell was mitigated or solved, the remaining failure modes (which did not have time for appearing in the ALT) will appear later on, thus resulting in a higher warranty time. In consequence, improved versions of these commercial solar cells will increase substantially the real warranty times.…”
Section: Discussionmentioning
confidence: 99%
“…The left column of Figure 13 shows that the solar cells with temperature soak alone ("Ref_Low", "Ref_Mid" and "Ref_High") experience two effects: a) a decrease of the shunt resistance and b) a rise of series resistance which increases with temperature. This impact of the temperature was not observed in commercial lattice-matched GaInP/Ga(In)As/Ge triple junction solar cells [3]. An interesting feature is observed when comparing the left (temperature soak only) with the right column of Figure 13, where the time evolution of the dark I-V curve of solar cells stressed by temperature but with periodical measurement of their dark I-V curve is presented: the deleterious effect of series resistance caused by the temperature soak in "Ref_IV_Low" and "Ref_IV_Mid" is counterbalanced by the current injection when measuring the dark I-V curve.…”
Section: Influence Of Temperature In the Degradation Processmentioning
confidence: 89%
“…The average value of the calculated dV/dT was used then to obtain the junction temperature of the solar cells inside the chamber. This method has been successfully applied in previous ALTs [2,3] and is further explained in [11]. With this information the temperature of the climatic chambers was properly set in order to get 125, 145 and 165 °C as junction temperatures of the solar cells (Tcell) with current injection.…”
Section: Accelerated Life Testmentioning
confidence: 99%
See 1 more Smart Citation